Method for constructing directional heat transfer path by utilizing graphene slurry laminar flow shearing and energy storage application

The directional heat transfer path is constructed through the shearing of graphene slurry, which solves the problem of low directional heat transfer efficiency of phase change energy storage composite materials, and realizes efficient and simple graphene skeleton preparation and production of high thermal conductivity composite materials, which improves the Thermal conductivity and porosity simplify the process flow.

CN119143122APending Publication Date: 2024-12-17BEIHANG UNIV

Patent Information

Application Number
CN202411144183.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The directional heat transfer efficiency of existing phase change energy storage composite materials is low, resulting in insufficient thermal conductivity and the inability to fully utilize the excellent thermal conductivity of graphene.

Method used

Directional heat transfer path is constructed through the shearing of graphene slurry, and a refrigeration extrusion device is used to generate strong shear force on the graphene nanosheet layer, causing it to deflect, and high in-plane thermal conductivity is obtained through lamination and molding. Graphene skeleton, high-thermal conductivity graphene-based phase change energy storage composite material is prepared after vacuum-assisted infusion of phase change material.

Benefits of technology

The orientation and thermal conductivity of graphene foam are improved, the preparation process is simplified, the cost is reduced, and the large-size and efficient graphene skeleton preparation is achieved, the thermal conductivity and porosity are improved, and the response speed is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143122A_ABST
    Figure CN119143122A_ABST
Patent Text Reader

Abstract

The invention relates to a method for constructing a directional heat transfer path by utilizing graphene slurry laminar flow shearing and energy storage application. By utilizing the laminar flow principle of liquid in a pipeline and utilizing the flow velocity difference of the liquid close to the inner wall of the pipeline and the middle part of the pipeline, a shearing force with zero graphene deflection is generated, so that a high-orientation graphene skeleton is prepared, and then the graphene skeleton with high thermal conductivity is obtained through high-temperature graphitization treatment. And filling the phase change energy storage material by using an RTM-like vacuum negative pressure filling method to obtain the graphene phase change energy storage composite material with high thermal conductivity. The high-orientation and high-heat-conductivity graphene phase change energy storage material has the heat conductivity up to 158 W / (m.K) and the phase change enthalpy value up to 320 kJ / L, and the heat conductivity and the phase change enthalpy value can be adjusted according to different requirements. Therefore, the novel graphene phase change energy storage material has a great application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite materials, and in particular to a method for constructing a directional heat transfer path by utilizing graphene slurry laminar shearing and energy storage applications. Background Art

[0002] Phase change energy storage technology is a technology that uses the phase change process of matter (such as solid-liquid phase change or liquid-gas phase change) to store and release energy. The development of this technology began in the 20th century and was initially mainly used for solar energy utilization and heat storage in residential heating systems. With the advancement of technology, the application scope of phase change energy storage materials has gradually expanded, covering multiple fields such as construction, transportation, and electronic manufacturing. Among them, phase change energy storage materials have significant advantages: 1. Energy saving and emission reduction: Phase change energy storage technology can effectively use renewable energy (such as solar energy) to store energy and release it when needed, thereby reducing the demand for traditional energy, reducing greenhouse gas emissions, and helping to address global warming and climate change issues; 2. Improve energy utilization efficiency: Phase change energy storage materials can improve the efficiency of energy utilization, achieve energy balance and stable supply by storing energy and releasing it when needed, and reduce energy waste; 3. Multi-field application: Phase change energy storage technology has broad application prospects in multiple fields such as construction, transportation, and electronic manufacturing, and can provide energy-saving and environmentally friendly solutions for various industries; 4. Sustainable development support: Phase change energy storage technology helps to support the goals of sustainable development, promote the utilization and promotion of clean energy, reduce dependence on non-renewable energy, and promote sustainable economic development. Considering the non-renewable, polluting and environmental problems of traditional energy resources such as oil, as well as concerns about resource depletion, it is particularly urgent to develop efficient storage and conversion of clean energy. Therefore, the development of phase change energy storage technology is of great significance, which can provide effective solutions to energy and environmental problems and promote the process of sustainable development.

[0003] At present, phase change energy storage composite materials are facing a very serious problem: low directional heat transfer efficiency. The key to solving this problem is to optimize the skeleton part of the composite material to obtain higher thermal conductivity. In this regard, graphene, a popular two-dimensional material, shows great potential because it has extremely high in-plane thermal conductivity (between 2000 and 5000 W / m·K). This material has been widely studied and applied in improving thermal conductivity. The unique two-dimensional structure of graphene causes its thermal conduction method to be different from that of conventional materials, which requires the skeleton structure of graphene to be highly directional in order to make full use of its excellent thermal conductivity properties. Summary of the invention

[0004] In response to the urgent need for phase-change energy storage composite materials with high thermal conductivity, the present invention provides a method for constructing a directional heat transfer path using laminar shear of graphene slurry and energy storage applications. First, the graphene slurry is concentrated or diluted, and the graphene slurry is extruded through a freezing extrusion device. Since the slurry will produce different flow rates at different heights during the flow process, a strong shear force is generated on the graphene nanosheet layer, causing the graphene nanosheet layer to deflect and highly orientate. After lamination and molding, a graphene skeleton with high in-plane thermal conductivity is obtained. The phase change material is infused in a vacuum-assisted infusion manner to obtain a graphene-based phase-change energy storage composite material with high thermal conductivity. It is specifically carried out in the following steps:

[0005] 1) Preparation of graphene / polyvinyl alcohol oriented composite material: 0.5wt%-15wt% graphene slurry and water-soluble polymer (the mass ratio of the two is 1:3) are mixed and placed in a planetary stirrer at a rate of 1000-5000r / min for 1.5h, during which the graphene and water-soluble polymer slurry is continuously heated at a temperature of 90°C until it becomes a paste-like solid (with a viscosity range of 50-2000mPa·s);

[0006] 2) Preparation of highly oriented graphene sheets: a pasty graphene / water-soluble polymer composite material is loaded into a heatable screw extruder, and extruded at a speed of 1-500 mm / min onto a drafting plate with a speed of 1-500 mm / min, with an extrusion port height (the height of the extrusion port is the distance from the extrusion die to the drafting plate) of 1-200 μm to obtain graphene / water-soluble polymer highly oriented sheets, and each layer of the obtained graphene / water-soluble polymer highly oriented sheets is then placed into a heatable mold;

[0007] 3) Preparation of highly oriented graphene skeleton: placing the graphene / water-soluble polymer highly oriented sheets in a heatable mold under a press, and making the contact between each sheet closer by molding to further obtain highly oriented graphene sheets, and also obtaining highly oriented graphene / water-soluble polymer composite materials of different densities (composite materials of different densities are obtained by molding to different thicknesses);

[0008] 4) Graphitization treatment of highly oriented graphene skeleton: placing the highly oriented graphene skeleton obtained in 3) into a graphitization furnace, and performing graphitization treatment for 3-35 hours in an inert gas atmosphere to remove the internal water-soluble polymer, thereby constructing a perfect graphene sheet and obtaining highly oriented graphene foams of different densities. The temperature of the graphitization treatment is 2300° C.-3200° C.;

[0009] 5) Infusing the phase change energy storage material into the graphene skeleton: placing the highly oriented graphene skeleton into the melted phase change material and placing it in a vacuum oven. Pumping the vacuum oven to -0.1MPa and maintaining it for 2-24h, a high thermal conductivity graphene phase change energy storage material is obtained under the action of the capillary and vacuum negative pressure;

[0010] Preferably, the graphene concentration in the above step 1) is 5wt%-15wt% for the best, and the water-soluble polymer can be starch, gum arabic, sodium alginate, bone meal, gelatin, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternary ammonium salt, polyethylene glycol, and one or more of them can be used;

[0011] Preferably, the extrusion speed in step 2) is 5-100 mm / min, which is optimal;

[0012] Preferably, the graphene skeleton graphitization treatment temperature in the above step 4) is 2800-3000° C., and 15-30h is optimal;

[0013] Preferably, the phase change material described in the above step 5) includes but is not limited to highly refined paraffin, n-heptacosane, n-tetradecane, dioctadecane, lauryl alcohol, adamantol, erythritol, oxidized polyethylene wax, etc., and one or more of them can be used.

[0014] The beneficial effects of the present invention are as follows: 1. The graphene skeleton prepared by the present invention and the traditional method is simpler and more efficient, and can be produced in large sizes and batches: the traditional method for preparing graphene skeletons is the ice template method. First, this method requires freeze drying, so it is impossible to prepare large-sized samples, because when the sample doubles in size, its freeze drying time will increase exponentially, so the cost will increase; secondly, when the ice template method is used to prepare large-sized samples, the temperature gradient is difficult to be transmitted to the edge of the large-sized sample, so the orientation degree at the edge of the sample is difficult to be uniform and low. This method can prepare large-sized, highly oriented graphene foams in batches, and it is simpler and more efficient. 2. The present invention improves the orientation degree of graphene foam: through the viscous flow of graphene slurry and thermoplastic polymer, laminar flow of viscous liquid occurs at the extrusion port, and the flow speeds of various parts of the extrusion port are different, so that the graphene sheets produce strong shear force, thereby obtaining highly oriented graphene foam. 3. The materials used in the present invention are simpler and more economical: the water-soluble thermoplastic polymer used in the present invention is cheap and used in small amounts. Compared with the traditional method of long-term use of freeze-drying and liquid nitrogen, the cost of this method is lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1It is a schematic diagram of the mechanism of fluid-oriented graphene sheets;

[0016] Figure 2 is a SEM picture of the oriented graphene skeleton of Example 1;

[0017] Figure 3 This is a Raman Mapping image of the high thermal conductivity graphene skeleton in Example 1. DETAILED DESCRIPTION

[0018] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0019] Embodiment 1:

[0020] The method for preparing the high thermal conductivity phase change energy storage composite material described in this embodiment is specifically carried out according to the following steps:

[0021] 1) Preparation of graphene / polyvinyl alcohol oriented composite material: 15% graphene slurry and water-soluble polymer polyvinyl alcohol (the weight ratio of the two is 1:3) are mixed and placed in a planetary stirrer at a rate of 2000r / min for 1.5h, during which the slurry of graphene and water-soluble polymer polyvinyl alcohol is continuously heated until it becomes a paste-like solid;

[0022] 2) loading the pasty graphene / polyvinyl alcohol composite material into a heatable screw extruder, extruding it at a speed of 50 mm / min onto a drafting plate with a speed of 100 mm / min, with an extrusion port height of 50 μm, to obtain a graphene / polyvinyl alcohol highly oriented sheet, and then placing each layer of the obtained graphene / polyvinyl alcohol highly oriented sheet into a heatable mold;

[0023] 3) Preparation of highly oriented graphene skeleton: The graphene / polyvinyl alcohol highly oriented sheets placed in a heatable mold are placed under a press with a pressure of 30T, and the contact between each sheet is made closer by molding to further obtain highly oriented graphene sheets (pressing speed is 3mm / min), and highly oriented graphene / polyvinyl alcohol composite materials with different densities (through different thicknesses) can also be obtained by molding;

[0024] 4) Graphitization treatment of highly oriented graphene skeleton: placing the highly oriented graphene skeleton obtained in 3) into a graphitization furnace, and performing graphitization treatment for 25 hours in an inert gas atmosphere to remove the internal polymer dispersant and polyvinyl alcohol, thereby constructing a perfect graphene sheet and obtaining highly oriented graphene foams of different densities (through different thicknesses), and the temperature of the graphitization treatment is 3000° C.;

[0025] 5) Infusing the phase change energy storage material into the graphene skeleton: placing the highly oriented graphene skeleton into the melted phase change material and placing it in a vacuum oven. Pumping the vacuum oven to -0.1 MPa and maintaining it for 24 hours, a high thermal conductivity graphene phase change energy storage material is obtained under the action of the capillary and vacuum negative pressure;

[0026] The graphene phase change energy storage material prepared in this embodiment 1 has a height of 10 mm and a diameter of 200 mm.

[0027] In this embodiment, by testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the fast-response high-orientation phase change energy storage composite material is 143W / (m·K), the latent heat of bulk phase change is 242kJ / L, the open porosity is 97%, and the orientation factor is 0.76. Compared with the traditional graphene / organic phase change energy storage material, the thermal conductivity is increased by 178%, the orientation factor is increased by two times, and compared with the commercial phase change composite material, the open porosity is increased by 18%, and the response speed is increased by 70%.

[0028] Embodiment 2:

[0029] In the method for preparing the highly oriented phase-change energy storage composite material described in this embodiment, only the concentration of the graphene slurry in step 1) is changed to 20%, and the remaining steps are the same as those in the first embodiment.

[0030] The height of the graphene phase change energy storage material prepared in this embodiment 2 is 10mm and the diameter is 200mm. This embodiment improves the contact between graphene sheets and reduces the interfacial thermal resistance by increasing the concentration of graphene slurry, and deflects more graphene nanosheets during the extrusion process, thereby improving their orientation and increasing thermal conductivity. By testing the in-plane thermal conductivity of the sample, it was found that the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material was 156W / (m·K), the latent heat of bulk phase change was 243kJ / L, the orientation factor was 0.88, and the open porosity was 95%.

[0031] Embodiment three:

[0032] In the method for preparing the highly oriented phase-change energy storage composite material described in this embodiment, only the extrusion speed in step 2) is changed to 500 mm / min, and the remaining steps are the same as those in the first embodiment.

[0033] The graphene phase change energy storage material prepared in this embodiment 3 has a height of 10 mm and a diameter of 200 mm. In this embodiment, by increasing the extrusion speed, the flow of the graphene slurry in the pipeline is turbulent, the deflection of the graphene nanosheet layer is reduced, and the orientation arrangement of the graphene during flow is reduced, so that the orientation degree of the graphene skeleton is reduced. The thermal conductivity of the obtained highly oriented graphene skeleton is 131 W / (m·K), and the latent heat of phase change is 242 kJ / L, the orientation factor is 0.65, and the open porosity is 95%.

[0034] Embodiment 4:

[0035] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the graphitization temperature in step 4) is changed to 3200° C., and the remaining steps are the same as those in the first embodiment.

[0036] The height of the graphene phase change energy storage material prepared in this embodiment 4 is 10mm and the diameter is 200mm. By increasing the graphitization temperature, the degree of defects in graphene is reduced, so that the intrinsic thermal conductivity of graphene is increased. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity graphene phase change energy storage composite material is obtained to be 158W / (m·K), and the latent heat of phase change is 242kJ / L, the orientation factor is 0.72, and the open porosity is 95%.

[0037] Embodiment five:

[0038] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the heat treatment time in step 4) is changed to 15 hours, and the remaining steps are the same as those in the first embodiment.

[0039] The height of the graphene phase change energy storage material prepared in Example 5 is 10 mm and the diameter is 200 mm. The graphitization time of graphene is reduced, so that the graphene reduces its own defect repair, and the rearrangement reaction of graphene itself is difficult to occur, thereby reducing the intrinsic thermal conductivity of graphene. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is obtained to be 112 W / (m·K), and the latent heat of phase change is 242 kJ / L, the orientation factor is 0.72, and the open porosity is 95%.

[0040] Embodiment six:

[0041] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this embodiment, only the oxidized polyethylene wax in step 6) is replaced with erythritol, and the remaining steps are the same as those in the first embodiment.

[0042] The height of the graphene phase change energy storage material prepared in Example 6 is 10 mm and the diameter is 200 mm. By testing the in-plane thermal conductivity of the sample, the in-plane thermal conductivity of the high thermal conductivity and high orientation phase change energy storage composite material is 142 W / (m·K), and the phase change latent heat is 320 kJ / L, the orientation factor is 0.73, and the open porosity is 95%. Different phase change materials have different enthalpy values, and different phase change materials can be used according to different needs.

[0043] Comparative Example 1

[0044] In the method for preparing the high thermal conductivity and high orientation phase change energy storage composite material described in this comparative example, only the concentration of graphene in step 1) is adjusted to 20%, and the remaining steps are the same as those in Example 1.

[0045] The graphene phase change energy storage material prepared in this comparative example has a height of 10 mm and a diameter of 200 mm. By testing the in-plane thermal conductivity of the sample, it is found that the in-plane thermal conductivity of the fast response high orientation phase change energy storage composite material is 101 W / (m·K), the bulk phase change latent heat is 212 kJ / L, the open porosity is 77%, and the orientation factor is 0.55.

Claims

1. A method for constructing a directional heat transfer path using graphene slurry laminar shearing, characterized in that: The following steps are involved: 1) Preparation of graphene / water-soluble polymer oriented composite material: 0.5wt%-15wt% graphene slurry was mixed with water-soluble polymer and placed in a planetary stirrer at a rate of 1000-5000r / min for 1.5h, during which the slurry of graphene and water-soluble polymer was continuously heated at a temperature of 90°C until it became a paste-like solid, and the mass ratio of graphene to water-soluble polymer was 1:3; 2) Preparation of highly oriented graphene sheets: loading a paste of graphene / water-soluble polymer composite material into a heatable screw extruder, extruding at a speed of 1-500 mm / min onto a drafting plate with a speed of 1-500 mm / min, with an extrusion port height of 1-200 μm, to obtain graphene / water-soluble polymer highly oriented sheets, and then placing each layer of the obtained graphene / polyvinyl alcohol highly oriented sheets into a heatable mold; 3) Preparation of highly oriented graphene skeleton: placing the graphene / water-soluble polymer highly oriented sheets in a heatable mold under a press, and using a molding method to make the contact between each sheet closer to further obtain a graphene skeleton with a higher orientation; 4) Graphitization treatment of highly oriented graphene skeleton: placing the highly oriented graphene skeleton obtained in 3) into a graphitization furnace, and performing graphitization treatment for 3-35 hours in an inert gas atmosphere to remove the highly water-soluble polymer inside, thereby constructing a perfect graphene sheet and obtaining a highly oriented graphene foam. The temperature of the graphitization treatment is 2300° C.-3200° C.; 5) Infusing phase change energy storage material into graphene skeleton: Place highly oriented graphene skeleton into melted phase change material and place in vacuum oven. Pump the vacuum oven to -0.1MPa and keep it for 2-24h. Then, under the action of capillary and vacuum negative pressure, high thermal conductivity graphene phase change energy storage material is obtained.

2. The method for constructing a directional heat transfer path by using graphene slurry laminar shearing according to claim 1, characterized in that: The graphene concentration in step 1) is between 5wt% and 15wt%.

3. The method for constructing a directional heat transfer path by using graphene slurry laminar shearing according to claim 1, characterized in that: The extrusion speed in step 2) is 5-300 mm / min.

4. The method for constructing a directional heat transfer path using graphene slurry laminar shearing according to claim 1, characterized in that: The graphitization temperature in step 4) is between 2800-3200° C. and the time is between 5-25 hours.

5. The method of constructing a directional heat transfer path by using graphene slurry laminar shearing according to claim 1, characterized in that: The phase change material described in step 5) is at least one of highly refined paraffin, n-heptacosane, n-tetradecane, dioctadecane, lauryl alcohol, adamantol, erythritol, and oxidized polyethylene wax.

6. According to the method for constructing a directional heat transfer path using graphene slurry laminar shearing as described in claim 1, the water-soluble polymer is at least one of starch, gum arabic, sodium alginate, bone meal, gelatin, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl alcohol, polymaleic anhydride, polyquaternary ammonium salt, and polyethylene glycol.

7. A high thermal conductivity phase change energy storage material of oriented graphene nanosheets prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method of continuously preparing graphene in screw machine by using supercritical fluid

    CN107298440A

  • Polyvinyl alcohol / graphene conductive nano-composite material and preparation and application thereof

    CN109294131A

  • High-thermal conductivity fast-response phase change energy-storage composite material and preparation method thereof

    CN109705817A

  • Graphene frame material with high density and strength and preparation method thereof

    CN110316725A

  • Continuous preparation method and system of graphene film with directional heat conduction function

    CN115744884A

Cited By

  • Directional heat-conducting shaped composite phase change material and preparation method thereof

    CN120464368A